Atypical leiomyoma: unusual locations and findings coupled with uncommon presentation - Agrawal, Rekha; Shintre, Hemant; Agrawal, Krishna; Agrawal, Aniruddh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Extrauterine leiomyomas are a rare phenomenon, and they present a great diagnostic challenge. Retroperitoneal leiomyomas remain asymptomatic for a variable period and usually present with wide variety of signs and symptoms. A 51 years old female was multiparous and had undergone a total laparoscopic hysterectomy along with a bilateral salpingo-oophorectomy about four years ago. She visited the outpatient department of a tertiary care hospital complaining of something coming out per vaginum and expressed difficulty in passing urine and also complained of stress urinary incontinence. Bimanual pelvic examination, ultrasonography (USG) and Magnetic resonance imaging (MRI) revealed a large oval shaped well defined solid mass completely filling the vaginal canal while compressing urinary bladder. Tumor marker levels were normal. Laparotomy with adhesiolysis and complete excision of retroperitoneal mass was performed. Frozen section followed by histopathology and immunohistochemistry confirmed that the mass was a leiomyoma. After surgical intervention and removal of mass, the symptoms dissipated and patient had a complete recovery. Despite hysterectomy the manifestation of leiomyoma appears to be apparent. Surgical excision of the mass appeared to be the correct move forward after the leiomyoma was diagnosed with the help of the MRI and the USG.